ANALISIS PSIKOLOGI TOKOH UTAMA DALAM NOVEL GENDUK KARYA SUNDARI MARDJUKI - Juniarti, Putri; Syam, Christanto; Seli, Sesilia (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstrackThe general problem of this research was the analysis of psychological prominent characters in novel genduk work by Sundari Mardjuki. It was delimited into four sub issues related to (1) id on the main character, (2) ego on the main character, (3) superego on the main character, and (4) the implementation plan at school. The aim of this research was to describe the id, ego, superego values associated with the God, others, own self, the nature and the implementation plan at school. This research used the descriptive method in the form of qualitative research. The data source was the collection of novel Genduk work by Sundari Mardjuki. The technique used in this research was documenter study, and the tool of data collection was the researcher herself as the key instrument. Based on the results of the data analysis, it was found that there were 32 data related to id on the main character, 40 data related to ego on the main character, and 39 data related to superego on the main character.Keywords: psychological, novel